La propiedad intelectual y los conocimientos tradicionales de la medicina utilizados durante la pandemia COVID-19 en las Comunidades Rurales del cantón Guaranda, en el año 2020-2021. - Agualongo Milan, Mercy Marisol (2023)
Traditional Knowledge is part of the indigenous peoples and communities that are forged throughout history and are transmitted from generation to generation and in some cases are perfected. In the rural areas of the Guaranda canton of the Bolívar province, traditional medicine is maintained due to being in a privileged climatic floor, where they cultivate different medicinal plants, for the curative use of different diseases, which in the Covid-19 pandemic were Of great help, among these sectors, Salinas de Guaranda stands out. Traditional knowledge is related to Intellectual Property, because if they receive patent, trademark and geographical indication protection or the form of trade secret or confidential information, they will help people benefit from these products. Thus, the importance of the issue lies in the knowledge and dissemination that the traditional knowledge of these peoples, being protected by Intellectual Property, can adequately benefit the original producers and generators of the same. Therefore, it is important to analyze how medicinal products help to improve the quality of life of people, among them it helped Covid-19, therefore, their knowledge is required, for their proper registration, and benefit of registration within the margins of intellectual property. Keywords: traditional knowledge, medicinal plants, intellectual property.